249 TEXTBOOK SURGICAL OUTCOMES IN ESOPHAGEAL CANCER: THE INFLUENCE OF NATIONAL KEY PERFORMANCE INDICATORS. (14th September 2020) - Al Azzawi, M; Bolger, J; Whooley, J; Trench, L; Allen, J; Bolger, E; Downey, E; Arumugusamy, M; Robb, W
Abstract:  : High quality surgery remains the cornerstone of treating esophageal malignancy. Recent work from the Dutch Upper-gastrointestinal Cancer Audit have defined ten surgical and perioperative "textbook" parameters that correlate with improved overall survival in patients undergoing esophageal resection. In 2013, national key performance indicators were introduced in Ireland against which esophageal cancer resection was to be benchmarked. This project examines the effect of introducing the KPIs on the proportion of patients attaining "textbook" outcomes for esophagectomy. Methods: A retrospective review of all esophagectomies and from January 2010 until June 2019 was performed. Clinical, pathological, perioperative, morbidity and mortality outcomes were recorded. 10 "textbook" parameters were studied pre- and post-KPI introduction. Results: 269 underwent esophagectomy, 77 pre-KPI and 192 post-KPI. There were no significant differences in age (67.6 vs 66.4 years, p = 0.6), gender (72% male, 28% female vs 67% male, 23% female, p = 0.43), ASA grade (p = 0.6) or tumour stage (p = 0.37) pre- and post-KPI. In the pre-KPI era, 13/77 (17%) patients achieved all ten textbook parameters, compared with 79/192, (41%, p = 0.001) post-KPI. This compares favourably to DUCA "textbook" data. There was an improvement in adequate lymphadenectomy (56% vs 83%, p = 0.002), a reduction in margin positivity (21% vs 7%, p = 0.001) and reduced peri-operative mortality (6% vs 2%, p = 0.03) post-KPI. Conclusion: There has been a significant improvement in perioperative outcomes in esophagectomy following the introduction of national KPIs in our unit. The number of patients achieving "textbook" outcomes is comparable with international standards. The identification of textbook parameters allows further focus for future quality improvement initiatives.